Methodological principles for the development of a new power cable - Soleša Dragan; Vladisavljević Radovan; Miloica Duško (Ekonomija: teorija i praksa, 2018)
The aim of the paper is to present the methodology model for the development of a new power cable. The presented model relies on information and communication technologies (ICT) that help in the process of collecting, analyzing and making decisions. The aim of the author of the presented model is to monitor business-production processes in real time. With the use of strong feedback systems, decision makers can direct further business flows with greater security. In this paper, we will show to what extent the analyzed companies are able to use the latest solutions in the field of information and communication technologies.